Successful communication - Deverell, Cyril S. (London : G. Bell, 1973)
This volume examines the elements of successful communication. It examines: what communication must do; where it goes wrong; communicating with groups; face-to-face; words on paper; the supervisors writing; other forms of communication and organisation and channels of communication.
lje 24/01/2019
Loans
Keywords: Communication in management; Business communication